2018
DOI: 10.12688/f1000research.14184.2
|View full text |Cite
|
Sign up to set email alerts
|

The convergent epidemiology of tuberculosis and human cytomegalovirus infection

Abstract: Although several factors are known to increase the risk of tuberculosis, the occurrence of tuberculosis disease in an infected individual is difficult to predict. We hypothesize that active human cytomegalovirus infection due to recent infection, reinfection or reactivation plays an epidemiologically relevant role in the aetiology of tuberculosis by precipitating the progression from latent tuberculosis infection to disease. The most compelling support for this hypothesis comes from the striking similarity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 134 publications
(101 reference statements)
2
32
0
Order By: Relevance
“…CMV seropositivity was independently associated with incident TB among transplant recipients. This is consistent with data describing increased TB risk associated with CMV, which has led to the hypothesis that CMV co-infection may expedite progression from LTBI to TB disease via T cell activation [8,9]. Further cohort studies and basic science research are needed to elucidate whether there is a causal association between CMV and TB, and to rule out residual confounding by ethnicity, socioeconomic status or immune susceptibility as alternative explanations.…”
supporting
confidence: 83%
“…CMV seropositivity was independently associated with incident TB among transplant recipients. This is consistent with data describing increased TB risk associated with CMV, which has led to the hypothesis that CMV co-infection may expedite progression from LTBI to TB disease via T cell activation [8,9]. Further cohort studies and basic science research are needed to elucidate whether there is a causal association between CMV and TB, and to rule out residual confounding by ethnicity, socioeconomic status or immune susceptibility as alternative explanations.…”
supporting
confidence: 83%
“…KLRC2 deletion is associated with reduced numbers of mature NK cells and increased susceptibility to HIV infection, certain autoimmune conditions, and cancer (46)(47)(48)(49). We hypothesize that increased susceptibility to TB disease in CMV + infants may result from loss of control of CMV replication and/or impairment of NK cell function due to KLRC2 gene deletions in some individuals (21). Among CMVinfants who went on to develop TB disease, we observed upregulation of transcripts associated with T cell activation, including LAG3 (28), which is induced during active TB in a nonhuman primate model (50).…”
Section: Discussionmentioning
confidence: 99%
“…20). Recent epidemiological evidence supports a role for CMV in the etiology of TB with notable similarity in the age-sex distribution between the 2 infections (21). Rates of CMV infection were higher among TB patients than healthy volunteers in studies of both Nigerian adults and Russian children and adolescents (22,23).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have reported that infection with CMV enhances the risk of HIV acquisition and disease progression, through expansion of activated CD8+ T-cells, depletion of naïve T-cells and T-cell senescence [11][12][13][14] . More recently, CMV has been implicated in the aetiology of TB, supported by epidemiological associations between the two diseases [17][18][19][20][21] . In Gambian infants, CMV infection induced profound CD8+ T-cell differentiation and activation which persisted up to 2 years after infection 31,32 .…”
Section: T-cell Activation Associates With Lower Mycobacterial Antigementioning
confidence: 99%
“…We hypothesize that increased susceptibility to TB in CMV+ infants may result from loss of control of CMV replication and/or impairment of NK cell function due to KLRC2 gene deletions in some individuals 17 .…”
Section: T-cell Activation Associates With Lower Mycobacterial Antigementioning
confidence: 99%